The Influence of e-Health Literacy and Anxiety on Cyberchondria In Early Adulthood Internet Users at the Pulogadung Police Dormitory - Rukmana, Bagas; Sovitriana, Rilla (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This study aims to determine whether there is an influence of e-health literacy and anxiety on cyberchondria in early adult internet users at the Pulogadung Police Dormitory. This study uses a quantitative method with a purposive sampling technique with predetermined respondent criteria. The questionnaire was distributed to 202 respondents who had entered early adulthood with an age range of 18-40 years, domiciled at the Pulogadung Police Dormitory, internet or social media users, and had searched for health information on the internet. The instruments used in this study were the electronic-Health Literacy Scale (e-HLS), Beck Anxiety Inventory (BAI), and Cyberchondria Severity Scale (CSS). Data processing in this study used the Kolmogorov-Smirnov normality test and hypothesis testing used multiple linear regression tests. Based on the test results of the e- health literacy variable on cyberchondria, the p value = <0.001 (p <0.05) with an R2 value = 31.5%, which means that the first hypothesis is accepted and there is a significant influence. On the anxiety variable on cyberchondria , the P value = <0.001 (P <0.05) with an R2 value = 35.9%, which means that the second hypothesis is accepted and there is a significant influence. In addition, the results of the multiple linear regression test show that e-health literacy and anxiety have an effect on cyberchondria in early adult internet users at the Pulogadung Police Dormitory.